2020
DOI: 10.1142/s0219887821500213
|View full text |Cite
|
Sign up to set email alerts
|

Solitons of Kählerian space-time manifolds

Abstract: We study solitons of almost pseudo symmetric Kählerian space-time manifold. It is considered that different curvature tensors like projective, conharmonic and conformal curvature tensors in almost pseudo symmetric Kählerian space-time manifolds are flat. It is shown that solitons are steady, expanding or shrinking under different relations of isotropic pressure, the cosmological constant, energy density and gravitational constant..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In an almost pseudo symmetric pseudo-projectively flat Lorentzian Kähler spacetime manifold admitting Einstein field equation with cosmological constant, the h-almost conformal Ricci-Bourguignon soliton (g, ξ, h, µ, Λ) for the dark fluid is shrinking, if p > (κρ 18. In an almost pseudo symmetric pseudo-projectively flat Lorentzian Kähler spacetime manifold admitting Einstein field equation with cosmological constant, the h-almost conformal Ricci-Bourguignon soliton (g, ξ, h, µ, Λ) for the dust fluid is shrinking, if p 19. In an almost pseudo symmetric pseudo-projectively flat Lorentzian Kähler spacetime manifold admitting Einstein field equation with cosmological constant, the h-almost conformal Ricci-Bourguignon soliton (g, ξ, h, µ, Λ) for the radiation fluid is shrinking, if p…”
Section: Definition 34 ([17]mentioning
confidence: 99%
See 1 more Smart Citation
“…In an almost pseudo symmetric pseudo-projectively flat Lorentzian Kähler spacetime manifold admitting Einstein field equation with cosmological constant, the h-almost conformal Ricci-Bourguignon soliton (g, ξ, h, µ, Λ) for the dark fluid is shrinking, if p > (κρ 18. In an almost pseudo symmetric pseudo-projectively flat Lorentzian Kähler spacetime manifold admitting Einstein field equation with cosmological constant, the h-almost conformal Ricci-Bourguignon soliton (g, ξ, h, µ, Λ) for the dust fluid is shrinking, if p 19. In an almost pseudo symmetric pseudo-projectively flat Lorentzian Kähler spacetime manifold admitting Einstein field equation with cosmological constant, the h-almost conformal Ricci-Bourguignon soliton (g, ξ, h, µ, Λ) for the radiation fluid is shrinking, if p…”
Section: Definition 34 ([17]mentioning
confidence: 99%
“…In 2020, Siddiqi and Siddiqui [20] investigated the geometrical features of a perfect fluid spacetime in terms of conformal Ricci soliton and conformal η-Ricci soliton with torse-forming vector field ξ. Praveena et al [19] published their study on solitons of almost pseudo symmetric Kählerian space-time manifold. In the paper they showed that solitons are steady, expanding or shrinking under different relations of isotropic pressure, the cosmological constant, energy density and gravitational constant.…”
Section: Introductionmentioning
confidence: 99%
“…We find that the values of the cosmological constant, the energy density, the gravitational constant, and the pressure at an isotropic pressure of 25 all affect the stability, growth, and shrinking of solitons. [ 13] RESEARCH METHODOLOGY Secondary sources, such as books, educational and development publications, government papers, and print and online reference materials, were our primary means of acquiring knowledge about the Kahlerian Einstein manifold.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Also, Conformal Ricci soliton in perfect fluid spacetime [23] is studied. Praveena et al [20] studied solitons in Kählerian space-time manifolds. As Ricci-Yamabe soliton is a scalar combination of Ricci and Yamabe soliton, it is fruitful to study it in the context of perfect fluid spacetime and obtain results that generalize the previously known results in perfect fluid spacetime.…”
Section: Introductionmentioning
confidence: 99%